Assessment of genetic diversity using mitochondrial DNA variation in Gir cattle of India - Nayak, Vivek Kumar; Pathak, Prajwalita; Mukherjee, Anupama (Indian Journal of Dairy Science, 2020)
The present study is carried out with the aim to study the genetic diversity of 60 Gir cattle in the newly adopted herd of NDRI on the basis of mitochondrial D-loop hyper variable region. The animals were purchased from 4 major locations-IGFRI-Jhansi, Bhilwara, Ajmer and Kisangarh. After aligning the sequences a total of 53 haplotypes were identified. The Overall haplotype Diversity was observed to be 0.996±0.003 which shows that the population is diverse. Nucleotide diversity ranged from 0.693 ±0.35 to 0.707± 0.35 with overall diversity of 0.704±0.34 across all 60 sequences and the average no. of nucleotide difference varied from 279.45±125.42 to 285.16±128.36. FST value is significantly different from 0 for all pair wise combinations representing significant amount of Genetic differentiation. FST estimates between the population shows that animals from Ajmer and Bhilwara are more genetically differentiated (0.02987) while animals from Kisangarh and Bhilwara are genetically more closer (0.00440). All the above results show substantial variability between populations. These findings can be used for designing proper breeding and management strategies for Gir cattle in NDRI Herd.